PENGARUH KEPEMIMPINAN LURAH TERHADAP PENINGKATAN KESADARAN MASYARAKAT DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN DI KELURAHAN BUHA KECAMATAN MAPANGET - BUYUNG, RIVALDY; OGOTAN, MARTHA; TAMPONGANGOY, DEYSI (JURNAL ADMINISTRASI PUBLIK, 2019)
The UN is a direct tax collected by the Central Government, but the results of its receipt are aimed at the interests of the community in the area concerned with the location of the tax object. However, there is a tendency towards the reluctance of the people of Buha Sub-District to pay the tax seen from various matters concerning the awareness of the community itself. Given the importance of the role of the community in bearing state funding, it is necessary to influence the leadership of the village head to be able to utilize the potential of land and building tax in his area and motivate his officials and the community to carry out their obligations in paying taxes. Therefore this study aims to determine the effect of village leadership on increasing public awareness in paying land and building taxes. Correlation of 0.284 (positive correlation) and from the results of testing the coefficient table for Lurah leadership variables of 0.307 with constants 29.007 can be seen hypothetically which states that there is an influence of Village Leadership on Public Awareness at a significant level of 1%.Keywords: Leadership, Public Awareness in Paying PBB